Deciphering Microbial Community Dynamics and Biochemical Changes During Nyons Black Olive Natural Fermentations - Penland, Marine; Deutsch, Stéphanie-Marie; Falentin, Hélène; Pawtowski, Audrey; Poirier, Elisabeth; Visenti, Giorgia; Le Meur, Christophe; Maillard, Marie-Bernadette; Thierry, Anne; Mounier, Jérôme; Coton, Monika (Frontiers in Microbiology, 2020)
French PDO Nyons table black olives are produced according to a traditional slow spontaneous fermentation in brine. The manufacture and unique sensorial properties of these olives thus only rely on the autochthonous complex microbiota. This study aimed at unravelling the microbial communities and dynamics of Nyons olives during a 1.5-year-long spontaneous fermentation to determine the main microbial drivers and link microbial species to key metabolites. Fermentations were monitored at a local producer plant at regular time intervals for two harvests and two olive types (organically and conventionally grown) using culture-dependent and metabarcoding (ITS2 for fungi, V3-V4 region for bacteria) approaches. Olives and brines were also sampled for volatile, organic acids and phenolic compounds. No major differences in microbiota composition were observed according to olive type or harvest period. Throughout the fermentation, yeasts were clearly the most dominant. ITS2 sequencing data revealed complex fungal diversity dominated by Citeromyces nyonsensis, Wickerhamomyces anomalus, Zygotorulaspora mrakii, Candida boidinii and Pichia membranifaciens species. Bacterial communities were dominated by the Celerinatantimonas genus while lactic acid bacteria remained scarce. Clear shifts in microbial communities and biochemical profiles were observed during fermentation and, by correlating metabolites and microbiota changes, four different phases were distinguished. During the first 7 days, phase I, a fast decrease of filamentous fungal and bacterial populations was observed. Between days 21 and 120, phase II, W. anomalus and C. nyonsensis for fungi and C. diazotrophica for bacteria dominated the fermentation and were linked to the pH decrease and citric acid production. Phase III, between 120 and 183 days, was characterized by an increase in acids and esters and correlated to increased abundances of Z. mrakii, P. membranifaciens and C. boidinii. During the last months of fermentation, phase IV, microbial communities were dominated by P. membranifaciens and C. boidinii. Both species were strongly correlated to an increase in the fruity esters and alcohol abundances. Overall, this study provides an in-depth understanding about microbial species succession and how the microbiota shapes the final distinct olive characteristics. It also constitutes a first step to identify key drivers of this fermentation.